Pesticides and pancreatic adenocarcinoma: A transversal epidemiological, environmental and mechanistic narrative review. Issue 12 (December 2022) - Brugel, Mathias; Carlier, Claire; Reyes-Castellanos, Gabriela; Callon, Sidonie; Carrier, Alice; Bouché, Olivier
Abstract: Pancreatic adenocarcinoma (PA) incidence is rising worldwide, especially in France. The evolution of known risk factors such as tobacco smoking, obesity, type 2 diabetes, chronic pancreatitis, or constitutional mutations is not sufficient to explain this trend. Pesticides are known risk factors in other malignancies. Previous studies have outlined pesticides' influence in PA, such as dichlorodiphenyltrichloroethane as plausible risk factors. The general population is directly or indirectly exposed to pesticides through air, food or water. Some of these chemicals may accumulate in the body all along lifetime and may harm carriers. The toxic mixing effects of these chemicals are not well documented. Several hypotheses have been put forward to explain how pesticides can induce indirect (fatty pancreas, induced diabetes) or direct (oxidative stress, cell damage) carcinogenesis in pancreatic cells through inflammation. A strong corpus exists acknowledging pesticides as a PA risk factor. However, published studies do not provide a sufficient level of evidence to prove causality and current prospective case-control studies are still ongoing.